SARS-CoV-2 Mpro responds to oxidation by forming disulfide and NOS/SONOS bonds - Patrick Y. A. Reinke; Robin Schubert; Dominik Oberthür; Marina Galchenkova; Aida Rahmani Mashhour; Sebastian Günther; Anaïs Chretien; Adam Round; Brandon Charles Seychell; Brenna Norton-Baker; Chan Kim; Christina Schmidt; et al. (Nature Communications, 2024)
Abstract The main protease (Mpro) of SARS-CoV-2 is critical for viral function and a key drug target. Mpro is only active when reduced; turnover ceases upon oxidation but is restored by re-reduction. This suggests the system has evolved to survive periods in an oxidative environment, but the mechanism of this protection has not been confirmed. Here, we report a crystal structure of oxidized Mpro showing a disulfide bond between the active site cysteine, C145, and a distal cysteine, C117. Previous work proposed this disulfide provides the mechanism of protection from irreversible oxidation. Mpro forms an obligate homodimer, and the C117-C145 structure shows disruption of interactions bridging the dimer interface, implying a correlation between oxidation and dimerization. We confirm dimer stability is weakened in solution upon oxidation. Finally, we observe the protein’s crystallization behavior is linked to its redox state. Oxidized Mpro spontaneously forms a distinct, more loosely packed lattice. Seeding with crystals of this lattice yields a structure with an oxidation pattern incorporating one cysteine-lysine-cysteine (SONOS) and two lysine-cysteine (NOS) bridges. These structures further our understanding of the oxidative regulation of Mpro and the crystallization conditions necessary to study this structurally.